Upaya meningkatkan pembelajaran passing bolavoli dengan metode game drill - Hari, Hari Pamungkas; Galing, Galing Cahya Adi Krisna; Dimas, Dimas Iqbal Pradita; Fahmi, Dwi Fahmi Muchtar; Ilmah, Nur Khozana Ilmah; Rubbi, Rubbi Kurniawan (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
The purpose of this study was to improve volleyball passing learning with the game drill method for class X students. This study is a quantitative descriptive study using the Classroom Action Research PTK method using the drill method. The subjects of this study were class X students of SMKN 1 Singsori, Malang Regency with a total of 25 students. This study was conducted in class X students of SMK N 1 Singosari, Malang Regency with the research subjects of class X students totaling 25 consisting of 14 male students and 11 female students. The research was conducted in 2 cycles. From the results of the Classroom Action Research for volleyball passing material, it turns out that the game drill method is able to improve previous learning. The researcher has reviewed the results of observations, field notes, and documentation stating that the results of the study indicate that in volleyball learning, especially passing, class X students of SMK N 1 Singosari, Malang Regency have increased. The results of cycle 1 action from the active sub-indicator from 68% to 90%, the happy sub-indicator from 68% to 95%, the spirit sub-indicator from 72% to 93%..